Meningkatan Minat Belajar Mengenal Huruf Hijaiyah Melalui Media Celemek Pada Anak Usia Dini di Gorontalo - Patingki, Yuliana; Pratiwi, Wiwik (Jurnal Euforia, 2025)
Introducing hijaiyah letters to children, an effective approach is through an introduction that does not burden children with the demands of reasoning letter by letter. Apron media is a medium that can support increasing interest in learning and the ability to recognize hijaiyah letters. This research uses a Classroom Action Research (PTK) approach which aims to improve the quality of education through a series of changes and encouraging teachers to reflect on their teaching practices. The results of the research showed that there was an increase in interest in learning to recognize hijaiyah letters through aprons in cycle I. It could be seen that, in the action of cycle I, meeting I, of the 12 children in group A, there were 10 children who showed results starting to develop (MB) and 2 other children had not yet developed ( BB). In cycle I, meeting II, 8 children who gave results developed according to expectations (BSH) and 4 other children whose results began to develop (MB). In cycle I, meeting III, 3 children showed very good development results (BSB), 6 children developed according to expectations (BSH) and 2 others began to develop (MB). Meanwhile, in cycle II, meeting I, the actions were still the same as in cycle I, meeting III, namely in the very well developing (BSB) category there were still 3 children, and 8 children in the developing according to expectations (BSH) category and 1 other child was starting to develop (MB). In the second cycle of action, all children had developed very well.